Rural areas in Poland from a demographic perspective - Biegańska Jadwiga (Bulletin of Geography. Socio-Economic Series, 2013)
The article presents an analysis and a critical assessment of rural areas in Poland in the years 1999-2011 from a demographic perspective. The analysis is based on indicators characterising population density, population structure by gender and age, migrations of population, and vital statistics. In order to classify and compare rural areas, the k-means method is employed. The sample of rural areas used in the study contains all 2,173 rural and urban-rural gminas (excluding urban parts) in Poland.